Comparison of transperitoneal and retroperitoneal robot partial nephrectomy for kidney tumors - Yongdeuk Seo; Su Hwan Kang; Taek Sang Kim; Dong Ha Kim; Seong Bin Kim (Kosin Medical Journal, 2023)
Background Surgical techniques for small kidney tumors have been developed for decades, from open to robotic surgery. There are two approaches for partial nephrectomy: transperitoneal and retroperitoneal. We divided robotic partial nephrectomy cases into transperitoneal robotic partial nephrectomy (TRPN) and retroperitoneal robotic partial nephrectomy (RRPN) and compared the outcomes. Methods We retrospectively evaluated patients who underwent robotic partial nephrectomy at our hospital between November 2019 and May 2022. We reviewed patients’ demographic and perioperative data. Results Seventy robotic partial nephrectomies were performed (35 TRPN and 35 RRPN). There were significant differences in operation time, estimated blood loss (EBL), tumor size, and the RENAL Nephrometry Score (RNS) between those who underwent TRPN and those who underwent RRPN. Larger tumors were noted in the TRPN group, and the RNS was higher. In contrast, the operation time was shorter, EBL was lower, and tumors were more likely to be located in the posterior and lower portions in the RRPN group than in the TRPN group. Conclusions In our study, RRPN had advantages over TRPN in terms of operation time and EBL. However, TRPN tended to be performed rather than RRPN for tumors that were more complex in terms of size or RNS. Although the choice between RRPN and TRPN depends on the surgeon's preference, RRPN seems effective for treating small kidney tumors if selected appropriately.